Robust Precoder Design for Two-Hop Relay Networks over Double Correlated Rician Channels - Zhen Luo; Shu Hung Leung; Xiang Bin Yu (2013 IEEE 78th Vehicular Technology Conference (VTC Fall), 2013)
In this paper, a statistically robust precoder design is presented for space-time coded multiple-input, multiple-output (MIMO) relay networks over double correlated Rician channels. We assume both the source and destination terminals are equipped with multiple-antenna, while a single antenna is used in distributed non-regenerative relay nodes for reducing feedback overhead and processing burden on relays. The precoding matrix at the source terminal and amplifying parameters of relay nodes are optimized to maximize the total signal-to-noise ratio (SNR) at the destination assuming only statistical channel state information (CSI) available at the transmission sides. The optimization problem can be efficiently solved by an iterative method, resulting in a single-beam mode source precoder and diagonal precoding matrix for relay nodes. Numerical results demonstrate that the proposed scheme outperforms the equal power allocation scheme and existing method with single antenna nodes.